Setting up a Nuchal Translucency Clinic: What Radiologists Need to Know. Issue 1 (March 2016) - Onyeacholem, Ifeanyi; Kleiner, Beth; Hull, Andrew D.; Chibuk, Jason; Romine, Lorene; Anton, Tracy; Pretorius, Dolores H.
Abstract : Abstract: The purpose of this article was to discuss the process of setting up a nuchal translucency (NT) screening clinic in clinical practice, how to interpret the information in combination with other clinical tests, what to do if abnormal results are obtained, and to illustrate some of the fetal anomalies that are associated with an increased NT. The NT was initially implemented to predict the likelihood of a fetus with Down syndrome. Maternal age can be combined with fetal NT and maternal serum biochemistry (free β-hCG and PAPP-A) at 11 to 14 weeks to identify about 90% of affected fetuses. Setting up a clinic to perform the NT screening requires certified physicians and certified sonographers. Certification can be obtained for both physicians and sonographers through Nuchal Translucency Quality Review and Fetal Medicine Foundation. Cell-free DNA testing is now altering what our patients are choosing to evaluate fetuses at risk for chromosomal anomalies and congenital anomalies. Common pitfalls to performing, interpreting, and conveying results of the NT are illustrated in this article. Nasal bone measurement, fetal anatomy examination and fetal echocardiography are tools that add sensitivity to the detection of chromosomal abnormalities. Examples of fetal anomalies discovered during the NT screening are also illustrated. Screening for obstetric complications is an additional benefit to the NT clinic.